Effect of Fusion to the LTB Carrier Protein on Coronavirus Spike Protein Vaccine Candidates Produced in Maize - Erin Egelkrout; Magdalena Maj; Rodrigo Manjarin; Gina Fake; Muneaki Watanabe; Jenna Williams; Nate Blanchard; John Walker; Celine Hayden; John Howard (Viruses)
Coronaviruses continue to disrupt health and economic productivity worldwide. Porcine epidemic diarrhea virus (PEDV) is a devastating swine disease and SARS-CoV-2 is the latest coronavirus to infect the human population. Both viruses display a similar spike protein on the surface that is a target of vaccine development. Despite the availability of commercial vaccines for both viruses, there is still a high occurrence of infections and a great need for enhanced efficacy and lower costs. We previously produced the PEDV spike protein (S) using transgenic maize, enabling a low-cost supply of the vaccine candidate. In this study, we (1) test orally delivered PEDV vaccine candidates in pigs to optimize the mucosal immune response; (2) generate the SARS-CoV-2 S1 protein in maize; and (3) perform structural characterization of the S1 protein for PEDV and SARS-CoV-2. We demonstrated high expression levels in maize of the S1 subunit of the SARS-CoV-2 spike protein, both with and without fusion to the heat-labile enterotoxin B (LTB) subunit. We found that the LTB fusion protein from both coronaviruses preferentially assembles into higher molecular weight multimers, consistent with the formation of trimers. For PEDV, administering the spike protein fused to LTB to young pigs elicited a higher level of mucosal IgAs compared to maize grain containing the S1 protein alone or controls. This suggests that fusing the coronavirus spike protein with LTB may provide better protection.